A METHODOLOGICAL APPROACH TO THE DEVELOPMENT OF ORGANIC FOOD PRODUCTION IN THE CONTEXT OF THE BUDGET CRISIS IN THE RUSSIAN FEDERATION - Ivan Sergeevich NOVIKOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this paper, we study classical and modern approaches to the formation of a scientifically based methodology for managing industrial processing of organic agricultural raw materials for the production of organic food. In the current crisis conditions in the Russian Federation of national budgets of all levels, the development of the organic food industry without a justified methodological approach is impractical. In most cases, the economy of organic production is not allocated to an independent field of study and is identified with the traditional economy of production, “organic food production” - there is industrial processing of organic raw materials in accordance with the requirements of organic production standards, isolated in space and subject to mandatory certification by specialized bodies quality control. We study the conditions for the development of organic production within an existing enterprise, as well as the mechanism for creating a separate unit for the production of organic food products. We show that industrial processing of organic products should be carried out on the basis of and strict observance of fundamental organizational and economic principles. In particular, while in traditional production deliveries can be seasonal or one-time, in organic food production a prerequisite must be guaranteed availability of suppliers or a hub of organic raw materials for at least a month of uninterrupted production. Moreover, the classical cluster approach in terms of organic production can be unrealizable and the author’s concept of cooperative development of organic food production (industrial processing of organic products) is preferable.